COMPARING THE EFFICACY OF SMARTPHONE ORTHODONTIC APPLICATION AND CONVENTIONAL ORTHODONTIC PRACTICE MANAGEMENT SOFTWARE IN TELANGANA - SHARIQ MOHIUDDIN, MOHD.; ASIMUDDIN, SYED; HALKATI, M.B.; ISHAQ MOHIUDDIN, MOHAMMED (International Journal of Psychosocial Rehabilitation, 2024)
The use of smartphones has enabled the clinicians to find apps for their own use, facilitate meaningful conversations with their patients and simplify patient record management. Orthodontic apps make smartphones useful tools in the practice of evidence-based medicine at the point of care in addition to their use in mobile clinical communication. The ability to download custom-built software applications (apps) has created new opportunities for orthodontists to integrate technology into clinical practice and patients to collect information about orthodontics and help them during their treatment. Material and Method: Fifty orthodontists were selected from Telangana population and were distributed with “SaralDent 4.5” practice management software for the computer and “ADC Ortho,” a custom-built application for Smartphone. In the present study, we have selected patients requiring orthodontic treatment while maintaining good oral hygiene practices. They were subjected to comparison between the use of “ADC Ortho” Smartphone app and “SaralDent 4.5” computer software.Results:In this study, the mean and standard deviation of all the ratings by orthodontists for Saral Dent and ADC Ortho were compared. Out of the ten questions asked, the ADC Ortho app was found to be better than Saral Dent software in five aspects. Saral Dent was better than ADC Ortho in three aspects. We have used the Mann-Whitney U test, and the test values for Overall Experience on using SaralDent and ADC Ortho were 3.6±0.49 (4.0) and 3.7±0.65 (4.0), respectively, with ‘U’ value 1175.0 and ‘P’ value 0.6022, which shows it is not significant. Conclusion:This study illustrates many of the technical qualities of smartphones and is highlighted by their direct comparison with those of computers in orthodontic practice management, as the platform for the app and software are different. Applications are on the rise, with many clinicians and allied health workers already adopting smartphones However, the extent to which Smartphones provide benefits due to their mobility has been significantly under investigated.